A SURVEY OF SEVERAL SPECTRAL LINES IN THE SPECTRA OF THE SUPERGIANT HD 14143 - Maharramov, Y. M. (Одеські астрономічні публікації, 2016)
Variations in the Ha, Hb, HeI, CII, SiIII, Al III, FeIII, NII, and OII lines in the spectrum of the star HD 14143 are investigated using observations carried out in 2013 with the 2-m telescope at the Shamakhy Astrophysical Observatory. It has been revealed an anti-correlation between the variability of the radial velocity and spectral parameters of the absorption and emission components of the Ha line in the spectrum of the star HD14143. Inaddition, such anticorrelation has also been found out between the variability of the radial velocities of HeI and CII lines. At the same time the variabilities of the radial velocities of the absorption component of the Ha and CII lines, as well as Hb and HeI lines correlate with each other.